2021
DOI: 10.54648/leie2021010
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Economic Sanctions and WTO Law: Examining the Adequacy of the National Security Exception

Abstract: Individual states increasingly rely upon targeted economic sanctions to achieve their foreign policy goals. The legality of such unilateral sanctions remains debatable in public international law. However, their proliferation and possible negative repercussions encourage targeted states to question their legality before international tribunals, including the World Trade Organization (WTO) dispute settlement system. Against this backdrop, the article analyses three types of recently enacted unilateral targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…127 This author has also argued that restrictions on information and communications technology and services, which target Huawei and which might be inconsistent with WTO obligations, could not always be justified under the WTO national security exceptions, as it is interpreted and applied by the WTO panels. 128 In 2021, China brought the issue of Sweden's restrictions on Huawei's participation in their 5G networks to the attention of the Council for Trade in Goods. 129 Recently, in April 2022, Belgium's draft law introducing additional security measures for the provision of mobile 5G services was labeled by China as a special trade concern and included in the Council for Trade in Goods agenda.…”
Section: Proceedings Before Domestic Agencies and Disputes Before Dom...mentioning
confidence: 99%
“…127 This author has also argued that restrictions on information and communications technology and services, which target Huawei and which might be inconsistent with WTO obligations, could not always be justified under the WTO national security exceptions, as it is interpreted and applied by the WTO panels. 128 In 2021, China brought the issue of Sweden's restrictions on Huawei's participation in their 5G networks to the attention of the Council for Trade in Goods. 129 Recently, in April 2022, Belgium's draft law introducing additional security measures for the provision of mobile 5G services was labeled by China as a special trade concern and included in the Council for Trade in Goods agenda.…”
Section: Proceedings Before Domestic Agencies and Disputes Before Dom...mentioning
confidence: 99%
“…The new Chinese laws prescribe the use of the two types of export restrictions as potential sanctions: either a complete prohibition of exports or an export license requirement as a precondition for exports. It is worth observing that export prohibitions (bans) as well as nonautomatic export licensing schemes, especially if they are administered in a non-transparent and discriminatory way, run afoul of the WTO commitments (Bogdanova, 2021). To be more specific, export bans on goods are inconsistent with the prohibition of quantitative restrictions enshrined in Article XI:1 of the GATT 1994, which has been interpreted broadly: "[T]he text of Article XI:1 is very broad in scope, providing for a general ban on import or export restrictions or prohibitions 'other than duties, taxes or other charges'" (Panel Report, India -Quantitative Restrictions).…”
Section: What Are the Broader Implications Of China's Shift In Use Of...mentioning
confidence: 99%
“…To be more specific, export bans on goods are inconsistent with the prohibition of quantitative restrictions enshrined in Article XI:1 of the GATT 1994, which has been interpreted broadly: "[T]he text of Article XI:1 is very broad in scope, providing for a general ban on import or export restrictions or prohibitions 'other than duties, taxes or other charges'" (Panel Report, India -Quantitative Restrictions). Restrictions on the exportation of services may be GATS-incompatible only if a WTO Member has undertaken market access commitments in a specific services sector and under mode 3, which also covers the right to export services to recipients abroad (Bogdanova, 2021). Regarding export license schemes, the panel in China -Raw Materials concluded that: "a licence requirement that results in a restriction […] would be inconsistent with GATT Article XI:1.…”
Section: What Are the Broader Implications Of China's Shift In Use Of...mentioning
confidence: 99%